Marketization, inequality, and institutional change: Toward a new framework for comparative employment relations. (April 2017) - Greer, Ian; Doellgast, Virginia
This article develops a framework for analyzing the social effects of marketization, defined as the imposition or intensification of price-based competition. The conceptual background is debates in comparative employment relations over the liberalization of markets and its consequences across Europe. Our central proposition is that marketization in its diverse forms leads to increased economic and social inequality via its effects on non-market institutions. We outline two mechanisms through which this happens. First, the means used by managers and investors to seek influence shifts from voice to exit, leading to the disorganization of industrial relations and welfare institutions. Second, economic activity shifts from productive toward non-productive activities, leading to changes in market regulation that are insulated from public scrutiny.